Delphi method - Proposal to calculate the number of experts in a Delphi study on biodegradable packaging to 2032 [Método Delphi - Propuesta para el cálculo del número de expertos en un estudio Delphi sobre empaques biodegradables al 2032] (2014)
This paper is about the Delphi method and provides elements to establish the influence of the number of experts when choosing priority themes and variables. For this purpose, a Delphi study was made in 2014 related to the issues, technologies and variables which have a priority in the year 2032 regarding biodegradable packaging. Such matter was evaluated over the original data and the incidence of the number of experts was assessed: 9, 15, 22 and 24. Furthermore, the estimate of the expert competence "k" coefficient was done and compared with the relation between the common core of issues obtained from the opinions of the group of 16 experts with the highest "k" coefficient. Amongst the key results, it can be observed that from the analysis with the 9 experts a common set of issues was presented, which remained constant for the other quantities of experts. In other words, increasing the number of experts did not present big changes on the priority issues. However, minor variations with 15 and 22 experts were obtained. As for expert competence "k" coefficient the results obtained with the 16 experts with a "k" coefficient greater than or equal to 0.8, in four of the five groups, high percentages were obtained with the common core priority issues, while experts with a lower "k" coefficient of 0.8 were placed in the five groups of high variation percentages, taking into account that they were given the same common core topics.